Adsorption of Reactive Blue 19 on coconut shell and bamboo activated carbons - Chieu, Le Van; Duy, Vu Ngoc; Tien, Nguyen Manh; Ha, Cao The (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3, 2017)
Abstract: Kinetics and isotherms of Reactive Blue 19 adsorption on two kinds of granular activated carbons from coconut shell and bamboo were determined in this study. These activated carbon are micropore materials with specific surface areas of 687 and 425 m 2 /g, respectively. Experimental data shows that equilibrium times are the same for both kinds of activated carbon when ininital concentration of the dye is 40 mg/L. However, maximum absorption capacity of bamboo activated carbon is about 10 times higher than that of coconut shell. This results reveals that adsorption site density on the surface plays a more important role than specific surface area.